Tooth mobility restriction by multistranded and CAD/CAM retainers: an in vitro study - Roser, Christoph; Rues, Stefan; Erber, Ralf; Hodecker, Lutz; Lux, Christopher J.; Scheurer, Carolien A. J. (European journal of orthodontics, 2023)
Orthodontic retainers should restrict physiological tooth mobility as little as possible. While this has been investigated for multistranded retainers, there is a lack of data for novel CAD/CAM retainers. To address this, the present study compared the restriction of physiological tooth mobility in multistranded retainers and different CAD/CAM retainers.One group of multistranded (n = 8) and five groups of CAD/CAM retainers (nickel-titanium (NiTi), titanium grade 5 (Ti5), polyetheretherketone (PEEK), zirconia (ZrO2), and cobalt-chromium (CoCr); each n = 8) bonded from canine to canine were investigated for their influence on vertical and horizontal tooth mobility using an in vitro model of a lower arch in a universal testing machine. Load-deflection curves were determined and statistically analysed.All retainers restricted tooth mobility to varying extents. The retainers had less of an influence on vertical tooth mobility, with less of a difference between retainers (14%-38% restriction). In contrast, significant (P ≤ 0.05) differences were observed between retainers in the restriction of horizontal tooth mobility. ZrO2 retainers had the greatest impact, restricting horizontal tooth mobility by 82% (68 ± 20 µm/100N), followed by CoCr (75%, 94 ± 26 µm/100N) and PEEK (73%, 103 ± 28 µm/100N) CAD/CAM retainers, which had comparable effects on horizontal tooth mobility. Ti5 (54%, 175 ± 66 µm/100N) and NiTi (34%, 248 ± 119 µm/100N) CAD/CAM retainers had less of an influence on horizontal tooth mobility, and were comparable to multistranded retainers (44%, 211 ± 77 µm/100N).This is an in vitro study, so clinical studies are needed to draw clinical conclusions. Multistranded and CAD/CAM retainers have different effects on tooth mobility in vitro. These effects should be further explored in future in vivo studies.
Gesehen am 12.03.2024